2021
DOI: 10.20961/jbb.v1i1.50384
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin E and Antioxidants Content of Portulaca oleracea L. Form Various Altitudes in East Java, Indonesia

Abstract: <p>This study aims to obtain purslane plants as a source of local food and a quality bioactive component from various altitudes in East Java, Indonesia. Purslane planting materials were collected from the lowlands &lt;200 m asl in Surabaya, medium plains 200-800 m asl in Malang DAU, and highlands&gt; 800 m asl in Batu, Malang. Analysis of vitamin E was as total tocopherol. The results of the analysis of the content of <em>Portulaca oleraceae</em> L. of vitamin E were as followed: in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…In the aqueous extract, the highest concentration of Gallic acid was 33.69 ppm, and the lowest concentration was for Kaempferol at 11.48 ppm. These findings are consistent with previous research [29] and indicate that Portulaca oleraceae L. is a potential source of local food of high quality With ingredients (active compounds) that have biological activity , including vitamin E and antioxidants. It has been highlighted in previous studies [20] that the phenolic compounds extracted from pomegranate peels contain a high percentage of Gallic acid in all the extracts, with a noticeable superiority in the alcoholic extract.…”
Section: Determination Of Active Compounds In Aqueous and Alcoholic E...supporting
confidence: 93%
See 3 more Smart Citations
“…In the aqueous extract, the highest concentration of Gallic acid was 33.69 ppm, and the lowest concentration was for Kaempferol at 11.48 ppm. These findings are consistent with previous research [29] and indicate that Portulaca oleraceae L. is a potential source of local food of high quality With ingredients (active compounds) that have biological activity , including vitamin E and antioxidants. It has been highlighted in previous studies [20] that the phenolic compounds extracted from pomegranate peels contain a high percentage of Gallic acid in all the extracts, with a noticeable superiority in the alcoholic extract.…”
Section: Determination Of Active Compounds In Aqueous and Alcoholic E...supporting
confidence: 93%
“…Finally, at a concentration of 250 mg/ml, all extracts showed 100% removal of hydrogen peroxide, indicating their potent antioxidant properties. These findings align with previous research [32], which demonstrated that Portulaca oleraceae L. used in disease treatment possesses natural antioxidants. Additionally, vitamin C acts as a scavenger for free radicals and can interact with superoxide anions, hydroxyl radicals, and lipid peroxides.…”
Section: Hydrogen Peroxide Antioxidant Activitysupporting
confidence: 93%
See 2 more Smart Citations